MICROBIOLOGICAL QUALITY OF SOME ICED. FISHES OF IMPHAL MARKET, MANIPUR - LILABATI, H.; VISHWANATH, W. (Journal of Indian Fisheries Association, 2015)
Imphal is the main marketing centre. of fish in Manipur. As fish production of the state. is not sufficient to meet the demands, about 120 metric tons of iced fishes are annually brought from other states and sold in this market. Microbiological quality of iced Wallago attu, abeo rohita; L. gonius and Aorichthys aor in respect of total fungal count (TFC), total plate Â·count of bacteria (TPC), Most Probable Number (MPN) of coliforms, Streptococci, Staphylococcus, Salmonella and Escherichia coli in four tissues viz skin, muscle, gill and intestine were analysed. In all cases, the counts were highest in the gills and lowest in the muscles. ’rhe values of TFC, TPC, coliforms, Streptococci and Staphylococci were Oa103/g 106-108/g, 2-a/g, 10-105/g, 10-105/g respectively. E. coli and Salmonella were not detected in any of the samples while. the ice used in the preservation contained 105 â€¢ 107 of TPC per gram. The microbiological quality of the iced fishes of Imphal market were .adjudged poor. The extremely high counts of bacteria might be due to (1) poor. quality nd left over fishes being packed, (2) cont ct with contaminated ice .and (3) repeated thawing and freezing during. the process of marketing and transportation.